THE CONCEPTS OF «ACCOUNTING» AND «FINANCIAL ACCOUNTING» AS THE PHENOMENA THE UNDERSTANDING OF THE GOALS OF MANAGEMENT - A. Bodyko (Вестник университета, 2017)
Logical reflection of this article is based on the definition of key positions, concepts «accounting» and «financial accounting» as the phenomena the understanding of the goals of management. In addition examines the causal basis of the problem of the relation of part and whole, coming from the quality of the originality and priority of the whole (the concept of «accounting»), with respect to its parts (the concept of Accounting and its specialized fields). Conclusions are made that the theoretical foundations of proper accounting «merge» with the theory of management, which in turn will become part of the economic theory. This transformation will revive political economy, but in the new methodological concept.